Three‐Dimensional Programmable Assembly by Untethered Magnetic Robotic Micro‐Grippers. (14th April 2014) - Diller, Eric; Sitti, Metin
<x xml:space="preserve">Abstract</x> Mobile sub‐millimeter micro‐robots have demonstrated untethered motion and transport of cargo in remote, confined or enclosed environments. However, limited by simple design and actuation, they lack remotely‐actuated on‐board mechanisms required to perform complex tasks such as object assembly. A flexible patterned magnetic material which allows internal actuation, resulting in a mobile micro‐gripper which is driven and actuated by magnetic fields, is introduced here. By remotely controlling the magnetization direction of each micro‐gripper arm, a gripping motion which can be combined with locomotion for precise transport, orientation, and programmable three‐dimensional assembly of micro‐parts in remote environments is demonstrated. This allows the creation of out‐of‐plane 3D structures and mechanisms made from several building blocks. Using multiple magnetic materials in each micro‐gripper, the addressable actuation of gripper teams for parallel, distributed operation is also demonstrated. These mobile micro‐grippers can potentially be applied to 3D assembly of heterogeneous meta‐materials, construction of medical devices inside the human body, the study of biological systems in micro‐fluidic channels, 3D micro‐device prototyping or desktop micro‐factories.